Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 9 - Quadratic Functions and Equations - Chapter Test - Page 593: 25



Work Step by Step

$kx^2-10x+25=0$ and $k\ne0$ $kx^2-5x-5x+25=0$ $x(kx-5)-5(x-5)=0$ The above formula is true when $k=1$, since we then have the following: $x(kx-5)-5(x-5)=0$ $x(x-5)-5(x-5)=0$ $(x-5)(x-5)=0$ Since both of the equations within the problem are the same, we can determine the only solution is $x=5$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.